Effect of multidisciplinary team model on prevention of PICC-associated thrombosis in cancer patients (多学科协作模式在肿瘤患者经外周静脉穿刺中心静脉置管相关性血栓预防中的应用研究) - GAN Jiemei (甘洁梅); CHEN Guolian (陈国连); ZHAO Zhiying (赵志莹) (Association of Integrative Nursing, 2023)
Objective　Methods non-synchronous control study including 162 patients were conducted. Patients were divided into control group and intervention group according to the time of admission. The control group (n=81) was given routine prevention program, while the intervention group was intervened by multidisciplinary cooperation mode, and the intervention program was developed to prevent thrombosis. The incidence of PICC-associated thrombosis, knowledge about thrombosis prevention and level of satisfaction were measured and compared between two groups. Results The incidence of thrombosis in the intervention group was lower than that in the control group(P＜0. 05). Scores of questionnaire on thrombosis knowledge and satisfaction in the intervention group were significantly higher than those in the control group(P＜0. 01). Conclusion By standardizing the procedure of diagnosis, treatment and nursing of thrombosis, multidisciplinary team model is aimed to reduce the incidence of thrombosis and improve the thrombosis-related awareness of inpatients with PICC placement. A　To investigate the application effect of multidisciplinary team model in preventing peripherally inserted central catheter (PICC)-associated thrombus in cancer patients. (目的 探讨运用多学科协作模式预防肿瘤患者经外周静脉穿刺中心静脉置管(PICC)相关性血栓的效果。方法 本研究为非同期对照研究, 按照入院时间将162名患者分为对照组与观察组, 各81例。对照组采用常规预防血栓方案, 观察组采用多学科协作模式进行干预, 制定干预方案对患者实施血栓预防。对比两组血栓发生率, 采用问卷调查两组患者血栓知识和满意度。结果 观察组PICC相关性血栓发生率低于对照组, 差异有统计学意义(P＜0. 05)。观察组血栓知识得分、满意度得分均高于对照组, 差异有统计学意义(P＜0. 01)。结论 多学科协作模式能使血栓诊疗及护理更规范, 有效降低PICC带管患者血栓发生率, 提高患者对血栓预防的认知。)